Proposal for management and dermoscopy follow-up of nevi in patients affected by oculocutaneous albinism type Ia - Rosario Peralta; Emilia Cohen Sabban; Paula Friedman; Carolina Marcucci; Luis A. Bollea Garlatti; Gastón Galimberti; Horacio Cabo (Mattioli1885, 2017)
Albino patients are at great risk for developing cutaneous neoplasms, including melanomas. In this paper we describe the dermatoscopic findings of nevi in two patients with oculocutaneous albinism type Ia (OCA-Ia) highlighting that they manifest a vascular pattern similar to that described for amelanotic melanoma. We propose managing these patients with dermoscopy, using the comparative approach, digital follow up (DFU), and reflectance confocal microscopy as a complementary tool for difficult cases.